(untitled) (Bangladesh Journal of Otorhinolaryngology, 2015)
Pedunculated angiolipoma is a rare benign tumor of upper aero digestive tract. We report a very rare case of pedunculated angiolipoma arising from hypopharynx which presented as a mass protruding outside the oral cavity. As the mass came out of mouth, patient was unable to close her mouth and suffered from difficulty in taking food. The mass was removed per orally under general anaesthesia and the patient was discharged in excellent condition. She is still under follow up and no recurrence since May 2012. Few cases are reported in literature but such a presentation is uncommon. DOI: http://dx.doi.org/10.3329/bjo.v20i1.22015 Bangladesh J Otorhinolaryngol; April 2014; 20(1): 35-38